1999
DOI: 10.1007/s10434-999-0144-y
|View full text |Cite
|
Sign up to set email alerts
|

The Progression of Melanoma Nodal Metastasis Is Dependent on Tumor Thickness of the Primary Lesion

Abstract: These results suggest that regional lymph node involvement may be dependent on the thickness of the primary tumor. As the primary tumor thickness increases, so does the likelihood of involvement of SLNs and higher regional nodes in the basin beyond the positive SLNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 9 publications
0
36
1
Order By: Relevance
“…There is, however, some measure of disagreement in published reports on the predictive value of micrometer-measured thickness of the primary melanoma. Some studies report that thin primary melanomas are associated with a low incidence of tumor spread beyond the sentinel node, [21][22][23][24][25] while others have not reported this correlation. 26,27 The algorithmic approach that we present is practical and yields reliable information.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, some measure of disagreement in published reports on the predictive value of micrometer-measured thickness of the primary melanoma. Some studies report that thin primary melanomas are associated with a low incidence of tumor spread beyond the sentinel node, [21][22][23][24][25] while others have not reported this correlation. 26,27 The algorithmic approach that we present is practical and yields reliable information.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that there may be some melanoma patients for whom CLND may not be necessary because nodal metastasis was never detected beyond the sentinel nodes [18][19][20]. We performed an analysis to determine, among patients with positive SLN, the frequency of nodal metastasis in the non-sentinel nodes (i.e., the nodes in the CLND specimen).…”
Section: Nodal Metastasis Beyond the Sentinel Nodesmentioning
confidence: 99%
“…[6][7][8][9][10][11] There is ample evidence supportive of a strong correlation between the thickness of the PCM and the metastatic capacity of spreading either via the draining lymphatic channels or hematogenously. 12,13 Once melanoma has metastasized by either route, the overall survival for patients greatly diminishes.…”
Section: The Impact Of Genomics In Understanding Human Melanomamentioning
confidence: 99%